KEWARISAN BERBASIS KEADILAN GENDER SEBAGAI IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS DALAM HUKUM EKONOMI SYARIAH - Tarmizi Tarmizi; Suandi Suandi; Lukman Ansar (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
Inheritance in Islam functions not only as a regulated mechanism for wealth distribution but also as an instrument for sustainable economic empowerment. Nevertheless, inheritance practices often overlook gender equality, limiting women’s access to economic resources and potentially hindering the achievement of the Sustainable Development Goals (SDGs). This study examines the dynamics of gender-equitable inheritance, its relevance to the SDGs, and the contribution of Islamic economic law in promoting gender justice. The findings indicate that the Qur’anic inheritance ratio of 2:1 requires contextual interpretation by considering public benefit (maslahah), distributive justice, and contemporary socio-economic realities. Such an approach provides opportunities for a more proportional and equitable distribution of inheritance. Gender-responsive inheritance practices contribute significantly to the achievement of SDG 5 (Gender Equality) and SDG 10 (Reduced Inequalities). From the perspective of Islamic economic law, equitable inheritance distribution can strengthen women’s economic empowerment while supporting the realization of maqasid al-shariah and sustainable development.